Optimization formula gastroretentive tablet of ranitidine HCl with floating system - Sulaiman, T.N. Saifullah; Fudholi, Achmad; Nugroho, A. Kharis (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Ranitidine HCl is an H-2 receptor antagonists for the treatment of peptic gastric secretion with a small bioavailability, so that should be developed in a sustained release dosage form are retained in the stomach. Ranitidine HCl floating tablet was formulation by effervescent system. Simplex lattice design was applied to optimize the formula of ranitidine HCl floating tablet by varying levels of Methocel K15M 100-185 mg, sodium bicarbonate 15-100 mg, and citric acid0-85 mg. The Optimum formula determined by superimposed contour plot from various parameters: flowability of granules, physical properties of tablet and drug release using Design-Expert®program. Based on superimposed contour plot obtained optimum formula for the area in the range of Methocel K15M 100-145 mg, sodium bicarbonate 20-80 mg and citric acid 25-80 mg.Key words: Ranitidine HCl, Gastroretentive, Simplex lattice design